CO2 assisted blending of poly(lactic acid) and poly(ε-caprolactone) - Murphy, S. H.; Marsh, J. J.; Kelly, C. A.; Leeke, Gary A.; Jenkins, M. J. (Elsevier, 2016)
Poly(lactic acid) (PLA) is gaining increasing interest from the packaging industry as a biodegradable alternative to oil based polymers such as polypropylene (PP) and polyethylene terephthalate (PET). However, its’ inherent brittle nature prevents widescale commercial use. Blending in order to improve the Young’s modulus, yield stress and elongation to break, provides a possible alternative although many polymers have been found to be immiscible with PLA. In this study, high pressure carbon dioxide (CO2) was utilised during blending to encourage miscibility between two normally immiscible polymers: poly(ε-caprolactone) (PCL) and poly(lactic acid) (PLA). Blends were prepared by melt blending in the presence of carbon dioxide (CO2) and compared to solvent casting and melt blending with a single-screw extruder. CO2 assisted blends demonstrated a significant reduction in the size and number of PCL domains in a PLA matrix, and consequently improved the adhesion between phases at the microscale. The optimum melt blend composition for Young’s modulus, yield stress and elongation to break was found to be 75% PLA and 25% PCL. Mechanical properties of PLA 2002D blends were further improved when prepared by CO2 assisted melt blending.
Keywords: Poly(lactic acid); Poly(ε-caprolactone); Blends; Carbon dioxide; Extrusion